LEMBAGA-LEMBAGA NEGARA - M. Farhan Akmal; Bunga Natasyah (Cahaya Ilmu Bangsa, 2025)
ABSTRAK State institutions are the division of duties to the government in power, where the ruler is not only one person or two people but consists of several institutions, organizations and so on. This material is studied in the State Administrative Law course, which discusses State Institutions starting from the central, city, and provincial levels, sub-districts and village. In the central government, there are three parts, namely legislative, executive, and judicial, which have different and separate tasks from each other, both in terms of duties and equipment that they perform. Indonesia's constitutional system has undergone changes after the amendment of the 1945 Constitution carried out by the MPR after the New Order. These changes are motivated by the will to build a democratic and balanced government among the branches of power, realize the rule of law and justice, and guarantee and protect human rights. This study uses a qualitative approach using a descriptive method. Data is collected through research from the internet, or secondary data data. The results of this study show that State Institutions are institutions formed to regulate the course of government. Where the Legislature (DPR), is tasked with making laws. The Executive (President and Vice President), is in charge of implementing or implementing laws. And the Judicial Institution (MA, MK, KY), is tasked with maintaining the implementation of the law. Abstrak Lembaga-lembaga Negara merupakan pembagian tugas-tugas kepada pemerintah yang berkuasa, dimana yang memerintah tidak hanya satu orang dua orang tetapi terdiri dari beberapa lembaga, organisasi dan sebagainya. Materi ini di pelajari pada mata kuliah Hukum Administrasi Negara, yang membahas tentang Lembaga-lembaga Negara mulai dari tingkat pusat, kota, dan provinsi, kecamatan dan desa. Pada pemerintahan pusat terbagi tiga yaitu legislative, eksekutif, dan yudikatif, yang memiliki tugas yang berbeda-beda dan terpisah satu sama lainnya, baik mengenai tugas maupun alat perlengkapan yang melakukan. Sistem ketatanegaraan Indonesia telah mengalami perubahan setelah adanya amandemen UUD 1945 yang dilakukan MPR pasca-Orde baru. Perubahan tersebut dilatarbelakangi adanya kehendak untuk membangun pemerintahan yang demokratis dan seimbang diantara cabang-cabang kekuasaan, mewujudkan supremasi hukum dan keadilan, serta menjamin dan melindungi hak asasi manusia. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode deskriptif. Data dikumpulkan melalui riset from internet, ataupun data data sekunder. Hasil penelitian ini menunjukkan Lembaga Negara merupakan Lembaga yang dibentuk untuk mengatur jalannya pemerintahan. Yang di mana Legislatif (DPR), bertugas untuk membuat undang-undang. Eksekutif (Presiden dan Wakil Presiden), bertugas menerapkan atau menjalankan undang-undang. Dan Lembaga Yudikatif (MA, MK, KY), bertugas mempertahankan pelaksanaan undang-undang.